2009
DOI: 10.1109/tnsre.2009.2029313
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Trajectory Decoding Using Motor Cortical Ensembles

Abstract: Although most brain-machine interface (BMI) studies have focused on decoding kinematic parameters of motion such as hand position and velocity, it is known that motor cortical activity also correlates with kinetic signals, including active hand force and joint torque. Here, we attempted to reconstruct torque trajectories of the shoulder and elbow joints from the activity of simultaneously recorded units in primary motor cortex (MI) as monkeys (Macaca Mulatta) made reaching movements in the horizontal plane. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 35 publications
1
88
0
Order By: Relevance
“…Ironically, one of the earliest multielectrode studies concluded that force and its first derivative were encoded more prominently in M1 than were movement kinematics (Humphrey et al 1970). A recent study found that torque computed for the shoulder and elbow joints during planar reaching movements was predicted only slightly less accurately than joint angular position or velocity (Fagg et al 2009). A direct comparison of end point kinematics and grip force found the latter to be predicted dramatically better (Carmena et al 2003), although EMG was predicted less accurately in that study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Ironically, one of the earliest multielectrode studies concluded that force and its first derivative were encoded more prominently in M1 than were movement kinematics (Humphrey et al 1970). A recent study found that torque computed for the shoulder and elbow joints during planar reaching movements was predicted only slightly less accurately than joint angular position or velocity (Fagg et al 2009). A direct comparison of end point kinematics and grip force found the latter to be predicted dramatically better (Carmena et al 2003), although EMG was predicted less accurately in that study.…”
Section: Discussionmentioning
confidence: 87%
“…In parallel, a small number of groups have begun to develop BMI applications based on the control of kinetic variables. One group found accuracy in joint torque predictions that was nearly comparable to kinematic predictions during planar reaching (Fagg et al 2009). Another study achieved predictions of electromyogram (EMG) activity that were of similar or greater accuracy than those typical of kinematic studies (Pohlmeyer et al 2007b).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For each file, we trained the Wiener cascade decoder on 9 min of data and tested it on the remaining minute. As a measure of performance, we calculated the mean fractional variance accounted for (VAF) between actual and decoded EMG over all 10 folds as follows (Fagg et al 2009):…”
Section: Decoding Methods and Performance Assessmentmentioning
confidence: 99%
“…One of the first successful closed-loop demonstrations decoded cursor position [7]. Since then, joint torques [8], angles [9] as well as grip action [10] have also been estimated.…”
Section: Introductionmentioning
confidence: 99%